CYBERBULLYING: NETIZENS' LANGUAGE INCIVILITY IN THE COMMENT SECTION OF GOSSIP ACCOUNTS - Lailiyah, Nur (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
This study aims to describe the language incivility of netizens on Instagram social media. This research uses a pragmatic cyber perspective and with qualitative descriptive methods, for the data collection process with the listen method, as well as recording techniques. Research data in the form of excerpts of speech in which there are manifestations of incivility. The source of data in this study comes from the words of netizens contained in the comment column of one of the posts on the Instagram gossip account. The results of this study show that there are incivility in the levity category, namely frivolity of the association subcategory with taboo expressions, frivolity of the cynicism subcategory with ridicule, frivolity of the pleonasm subcategory with jokes, frivolity of the subcategory of teasing with jokes, and frivolity of the subcategory of mocking with jokes.